A physiological evaluation of the efficiency of playing the wind instruments – an aerodynamic study - PAWŁOWSKI, Zygmunt; ŻÓŁTOWSKI, Marek (Archives of Acoustics, 1987)
The purpose of this study was to present mean values of particular aerodynamic parameters to determine the physiological standard of playing. The authors applied the aerodynamic method in examinations of musicians playing the orchestral wind instruments. Direct results of the measurements for each person were the following quantities: the pressure before the instrument inlet (SP), the mean air flow rate (MFR) through the mouthpiece or the reed, and the play time (MPT). On the basis of these quantities, the lips or reed resistance (GR), the expiration power (EP) and the work performed during playing (5) were calculated. The measured results were so elaborated that the measured results were calculated separately for those persons for whom the play time was no less than the mean time of persons playing the same instrument. For such a division of the examined persons, the mean values of the aerodynamic parameters were calculated. The efficiency of playing is essentially affected by the value of the lips or reed resistance (GR).